Do our newly graduated medical doctors have adequate knowledge about neonatal resuscitation? - Carlotti, Ana Paula de Carvalho Panzeri; Ferlin, Maria Lúcia Silveira; Martinez, Francisco Eulógio (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Neonatal resuscitation should be part of medical school curriculums. We aimed to evaluate medical school graduates’ knowledge of neonatal resuscitation. DESIGN AND SETTING: Cross-sectional study on the performance of candidates sitting a medical residency exam at Hospital das Clínicas, Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo, in 2004. METHODS: There were two questions on neonatal resuscitation. One question in the theory test aimed at evaluating basic knowledge on the initial approach towards newly born infants. The question in the practical exam was designed to evaluate the candidate’s ability to perform the initial steps of resuscitation and to establish bag-mask ventilation. RESULTS: Out of 642 candidates from 74 medical schools, 151 (23.5%) answered the theory question correctly. Significantly more physicians from public medical schools in the State of São Paulo answered correctly than did those from other schools in Brazil (52.5% versus 9.2%; p < 0.05). A total of 436 candidates did the practical exam. The grades among graduates from medical schools belonging to the State of São Paulo were significantly higher than among those from other schools (5.9 ± 2.6 versus 4.1 ± 2.1; p < 0.001). The grades for the practical question among candidates who had answered the theory question correctly were significantly higher than those obtained by candidates who had given wrong answers (p < 0.05). CONCLUSION: Medical school graduates’ knowledge of neonate resuscitation in the delivery room is quite precarious. Emphasis on neonatal resuscitation training is urgently needed in medical schools.